Novel Trimethoprim-Based Metal Complexes and Nanoparticle Functionalization: Synthesis, Structural Analysis, and Anticancer Properties - Abbas M. Abbas; Hossam H. Nasrallah; A. Aboelmagd; W. Christopher Boyd; Haitham Kalil; Adel S. Orabi (Inorganics)
In this study, we synthesized a novel trimethoprim derivative, 4-(((2-amino-5-(3,4,5-trimethoxybenzyl) pyrimidine-4-yl)imino)methyl)benzene-1,3-diol (HD), by the reaction of trimethoprim with 2,4-dihydroxybenzaldehyde. We then prepared metal complexes of this derivative with Cu(II), Co(II), Ni(II), Ag(I), and Zn(II) and functionalized them with ZnO and Au nanoparticles. Their structures were confirmed through 1H NMR, mass spectrometry, FTIR, conductivity, thermal analysis, magnetic susceptibility, X-ray diffraction, UV-Vis spectroscopy, and TEM, revealing octahedral geometries for all complexes. Surface features were investigated using density functional theory (DFT) analysis. Pharmacokinetic parameters and target enzymes for HD and its complexes were computed using the SwissADME web tool, with the BOILED-Egg model indicating that HD and its Cu complex should be passively permeable via the blood-brain barrier and highly absorbed by the gastrointestinal tract (GIT), unlike the Ni, Co, Ag, and Zn complexes, which are predicted to show low GIT absorption. Molecular docking studies with the Caspase-3 enzyme (PDB code: 3GJQ) using the AutoDock 4.2 software demonstrated binding energies of −7.66, −8.36, −9.05, −8.62, −6.90, and −7.81 kcal/mol for HD and the Cu, Co, Ni, Ag, and Zn complexes, respectively, compared to −6.54 and −4.63 kcal/mol for TMP and 5-FU (5-fluorouracil), indicating a potential superior anticancer potential of the novel compounds. The anticancer activities of these complexes were evaluated using the MTT assay. The IC50 values for 5-FU, TMP, HD, Cu-HD, HD@ZnONPs, Cu-HD@ZnONPs, HD@AuNPs, and Cu-HD@AuNPs were found to be 32.53, 80.76, 114.7, 61.66, 77, 53.13, 55.06, and 50.81 µg/mL, respectively. Notably, all derivatives exhibited higher activity against the HepG-2 cancer cell line than TMP, except for HD, which showed similar effectiveness to TMP. Real-time PCR analysis revealed that the Au-HD@AuNPs and Cu-HD@AuNPs significantly increased caspase-3 inhibition by 4.35- and 4.5-fold and P53 expression by 3.05- and 3.41-fold, respectively, indicating enhanced pro-apoptotic gene expression and apoptosis induction in HepG2 cells. Our findings demonstrate that these novel derivatives possess significant anticancer properties, with some complexes showing superior activity compared to standard drugs such as 5-Fluorouracil (5-FU) and Trimethoprim (TMP). This study highlights the potential of these nanocomposites as promising candidates for cancer therapy.